Intraprostatic Injection of Alcohol Gel for the Treatment of Benign Prostatic Hyperplasia: Preliminary Clinical Results - Benjamin T. Larson; Nelson Netto; Christian Huidobro; Marcelo Lopez de Lima; Wagner Matheus; Cristian Acevedo; Thayne R. Larson (The Scientific World Journal)
Benign prostatic hyperplasia (BPH) is one of the most common diseases ailing older men. Office-based procedures offer the advantage of being more effective than medications, while limiting the adverse effects, cost, and recovery of surgery. This study presents preliminary data on a new procedure that utilizes intraprostatic alcohol gel injection to ablate prostatic tissue. The purpose of this study is to evaluate the feasibility of using this gel as a treatment for BPH.